The Effect Of Cash Turnover And Profitability On Financial Performance At PT.Golden Great Borneo Lahat Branch - Fauzan Luthfi Saputra; Iskandar Malian; Hayani Hayani (Journal of Management, Economic, and Accounting, 2026)
The objectives of this research include: to determine the effect of cash turnover on financial performance at PT.Golden Great Borneo Lahat Branch,to determine the effect of profitability on financial performance at PT.Golden Great Borneo Lahat Branch and to determine the effect of cash turnover and profitability on financial performance at PT.Golden Great Borneo Lahat Branch. The sample of this research is PT Golden Great Borneo Lahat Branch with a period of 5 years from 2020-2024. This research uses qualitative research, using data sources including: primary data, secondary data, population and samples. Data collection methods used are: observation, interviews and distribution of questionnaires to a number of respondents. As well as using validity and reliability measuring tools, analysis prerequisite tests,then using data analysis methods using multiple regression analysis, hypothesis testing in the form of t-tests and F-tests. As well as correlation coefficients and determination coefficients. Data analysis in this study uses SPSS 23.0. From the results of the study,it is seen partially with the t test that the cash turnover variable with t count> from t table or 4.440>2.571 or sig t <0.03 then Ho is rejected and Hi is accepted,this shows that there is a significant influence between the cash turnover variable on the financial performance variable at PT Golden Great Borneo Lahat Branch and probability with t count> from t table or 6.909>2.571 or sig t <0.01 then Ho is rejected and Hi is accepted, this shows that there is a significant influence between the profitability variable on the financial performance variable at PT Golden Great Borneo Lahat Branch. From the test results, the F count value is greater than F table (15.492>9.01).This shows that the cash turnover variable and the profitability variable simultaneously have a significant effect on the financial performance variable. The test was carried out with a 95% confidence level. The simultaneous linear relationship between cash turnover and profitability variables and financial performance variables at PT Golden Great Borneo,Lahat Branch,is significant.